1993
DOI: 10.1111/j.1365-2125.1993.tb04160.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics, tolerability and pharmacodynamics of tucaresol (589C80; 4[2‐formyl‐3‐hydroxyphenoxymethyl] benzoic acid), a potential anti‐sickling agent, following oral administration to healthy subjects.

Abstract: (67) ,ug m1-1, respectively, at the highest dose. Median tmax in plasma was 6.5 h and in erythrocytes 24.5 h, when approximately 60% of the administered dose was in the target tissue. Plasma drug concentrations fell biexponentially with commencement of the apparent terminal elimination phase at approximately 24 h. The terminal elimination half-life from plasma increased with dose (r = 0.77; P < 0.0001) from 133-190 h at 400 mg to a mean (s.d.) of 289 (30) h at 3600 mg. Erythrocyte drug concentrations declined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 11 publications
3
33
0
Order By: Relevance
“…This provides an advantage in the application of this drug in pDNA vaccination protocols. Furthermore, since tucaresol has been shown to be systemically active (30,33), there may be no need for local coadministration of pDNA and tucaresol, as shown here by combining i.m. pDNA injection with s.c. injection of tucaresol.…”
Section: Vol 70 2002 Enhancement Of Dna Vaccination By Tucaresol 6655mentioning
confidence: 93%
See 3 more Smart Citations
“…This provides an advantage in the application of this drug in pDNA vaccination protocols. Furthermore, since tucaresol has been shown to be systemically active (30,33), there may be no need for local coadministration of pDNA and tucaresol, as shown here by combining i.m. pDNA injection with s.c. injection of tucaresol.…”
Section: Vol 70 2002 Enhancement Of Dna Vaccination By Tucaresol 6655mentioning
confidence: 93%
“…This costimulatory function results in a covalent and reversible reaction that works via binding to the amine-rich groups on T cells, which leads to T-cell-receptor-independent signaling (7). The effect of tucaresol is thought to be CD2 mediated (7,29,32,33). Our observations demonstrate that this approach is able to overcome the low efficacy commonly associated with pDNA-based vaccination (11).…”
Section: Vol 70 2002 Enhancement Of Dna Vaccination By Tucaresol 6655mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that tucaresol binds to cell surface molecules on the T cells and provides a costimulatory signal which is different from that induced by TCR signaling (7). Nonetheless, tucaresol has been clinically used and proven to be efficiently taken up and to be safe even in doses substantially higher than those used here (27,28). This could provide a significant incentive for clinical testing of a vaccine combination that contains a P-NP-based pDNA and tucaresol.…”
mentioning
confidence: 99%